ANTIBIOGRAM OF METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) STRAINS FROM KINDIRMO IN NASARAWA, NASARAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Dairy products have been found to be a major vehicle for the transmission of multidrug-resistant MRSA strains to man. This study determined the antibiogram of methicillin-resistant Staphylococcus aureus (MRSA) strains from traditionally-pasteurized dairy product (Kindirmo) in selected parts of Nasarawa, Nasarawa State, Nigeria. One hundred and sixty kindirmo samples were collected from vendors using random sampling from the areas selected for the study. Sample collection was between January 2021 and April 2021. Each sample was collected into sterile screwed-capped plastic bottle and labeled appropriately. Standard microbiological procedures were used in isolating and identifying MRSA strains from the samples. Characterisation of the MRSA strains was carried out using Microgen® kits. The MRSA strains were evaluated for their susceptibility to cefoxitin (30µg), clindamycin (2µg), chloramphenicol (30µg), doxycycline (30µg), gentamicin (10µg), sulphamethoxazole/trimethoprim (25µg), tobramycin (30µg), and vancomycin (30µg), using the Kirby-Bauer technique. Of the 160 samples examined, eight MRSA strains were obtained, giving a prevalence of 5.0%. All of the MRSA strains were resistant to cefoxitin (0-1mm); 62.5% were resistant to tobramycin (7-11mm); and 25.0% were resistant to chloramphenicol (4-10mm). Five (5) antibiotic resistant phenotypes were recorded among the MRSA strains. The occurrence of MRSA in Kindirmo as recorded in this study, suggest that, the consumption of the product constitute a hazard to consumers. Basic hygiene requirements during production and selling of the product should be imposed by relevant authorities. This will go a long way in ensuring the safety of the product.
Keywords: Antibiogram; MRSA; Dairy Product; Nasarawa; Nigeria